Tensile loading of a second-order elastic biogel - Soh, Jervis Kah Sheng (Nanyang Technological University, 2024)
Understanding the mechanical behavior of soft materials is crucial for various engineering applications, particularly in fields such as soft robotics and tissue engineering. This study explores the concept of energy density function and its relevance in characterizing the elastic properties of soft materials.